Hierarchically assembled microspheres consisting of nanosheets of highly exposed (001)-facets TiO2 for dye-sensitized solar cells. Issue 17 (3rd February 2016) - Peng, Jia-De; Lin, Hsi-Hsin; Lee, Chi-Ta; Tseng, Chuan-Ming; Suryanarayanan, V.; Vittal, R.; Ho, Kuo-Chuan
Abstract : Mono-dispersed 2D nanosheets of 3D microspheres nanostructure was synthesized. It shows highly exposed (001)-facets ( ca. 82%) and high surface area (112.2 m 2 g −1 ). 11.13%-efficient DSSC is obtained with TiO2 microspheres working electrode. Abstract : In this work, the mono-dispersed TiO2 microspheres with highly exposed (001)-facets ( ca. 82%), high surface area (112.2 m 2 g −1 ), and self-ordered 3D porous network have been rapidly synthesized by an in situ facet-controlling approach without any organic templates and employed as photoanodes of dye-sensitized solar cells (DSSCs). Owing to the stacking of 3D nanosheets of microspheres, the self-ordered internal porous network ( ca. 30 nm) provides an efficient pathway for electrolyte and dye molecules penetrating into the interior part of a microsphere. Besides, the large voids among microspheres ( ca. 300 nm) establish a highway for electrolyte diffusion. The formation processes of the prepared microspheres have been discussed, in which oriented self-assembly is involved. A reasonable mechanism is proposed to explain its high dye loading capacity (dye loading per gram/surface area of TiO2 ). Furthermore, according to the difference of normalized photocurrents of the cells with (001)-facet TiO2 and Ref-TiO2, the long wavelength region (600 to 800 nm) contributes 67.5% of the integrated photocurrent density; this result confirms its superior light scattering property. Finally, under 100 mW cm −2 light irradiation, a high photoelectric conversion efficiency of about 11.13% was achieved, as compared to that of the cell with a Ref-TiO2 film (8.11%). In light of their successful application in high-performing I3 − /I − -based DSSCs, it is envisaged that these TiO2 microspheres with highly exposed (001)-facets can be used as excellent semiconductor materials in mass transfer limited cobalt-based DSSCs, and also in other fields, such as photocatalysis, water splitting, and lithium ion battery.